Conformational changes induced in Hoxb-8/Pbx-1 heterodimers in solution and upon interaction with specific DNA. - Sánchez, M (1997)
Two classes of homeodomain proteins, Hox and Pbx gene products, have the ability to bind cooperatively to DNA. In Hox proteins, the homeodomain and a highly conserved hexapeptide are required for cooperative DNA binding. In Pbx, the homeodomain and a region immediately C terminal of the homeodomain are essential for cooperativity. Using fluorescence and circular dichroism spectroscopy, we demonstrated that Hox and Pbx proteins interact in the absence of DNA. The interaction in solution is accompanied by conformational changes. Furthermore, upon interaction with specific DNA, additional conformational changes are induced in the Pbx-1/Hoxb-8 heterodimer. These data indicate that prior to DNA binding, Hox-Pbx interaction in solution is accompanied by structural alterations. We propose that these conformational changes modulate the DNA binding properties of these proteins, ultimately resulting in cooperative DNA binding.